2013
DOI: 10.1080/03079457.2013.816654
|View full text |Cite
|
Sign up to set email alerts
|

Chicken embryo lethality assay for determining the virulence ofRiemerella anatipestiferisolates

Abstract: Riemerella anatipestifer is the causative agent of polyserositis and septicaemia in waterfowl. Twenty-one serotypes have been reported, and there is a strong variation in virulence between strains according to serotype or strain. However, little information is available to assess virulence, such as virulence-associated genes; thus, it is difficult to estimate the risk from field strains. Hence, we established a chicken embryo lethality assay (ELA) model to determine the virulence of R. anatipestifer strains. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 15 publications
11
22
0
Order By: Relevance
“…In this work, we demonstrate that embryonated eggs are highly susceptible to P. insidiosum infection via the allantoic cavity in a dose‐ and age‐dependent manner. We observed that increased zoospore concentration causes a decrease in survival time, and infection of embryos at a later embryonic day (14) showed delayed mortality, which agrees with the observations of Jacobsen et al and Seo et al when they inoculated chicken embryos with A. fumigatus and Riemerella anatipestifer respectively. Cell‐mediated immunity in chicken embryos has been demonstrated to start by 12th‐15th day of development by T‐cell colonisation of the spleen .…”
Section: Discussionsupporting
confidence: 91%
“…In this work, we demonstrate that embryonated eggs are highly susceptible to P. insidiosum infection via the allantoic cavity in a dose‐ and age‐dependent manner. We observed that increased zoospore concentration causes a decrease in survival time, and infection of embryos at a later embryonic day (14) showed delayed mortality, which agrees with the observations of Jacobsen et al and Seo et al when they inoculated chicken embryos with A. fumigatus and Riemerella anatipestifer respectively. Cell‐mediated immunity in chicken embryos has been demonstrated to start by 12th‐15th day of development by T‐cell colonisation of the spleen .…”
Section: Discussionsupporting
confidence: 91%
“…We also detected RA in the cloacae of 2% of wild ducks. Cloacal isolates of RA have also been reported (Seo et al 2013), and Xie et al (2010) detected RA in cloacae by real-time PCR 3 h to 5 days after subcutaneous inoculation. This suggests that RA could be shed in feces of wild birds.…”
Section: Discussionmentioning
confidence: 97%
“…However, relatively high costs, complexity and ethical considerations limit the application of such challenge tests. Therefore, it seems appropriate to use the chicken embryo lethality assay (ELA), which can provide an alternative tool to study the virulence of different strains in a faster, more sensitive, less expensive, more specific and relatively simple form (Wooley et al, 2000;Oh et al, 2012;Seo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Chicken ELA has been proposed to determine the degree of virulence of isolated fungi (Jacobsen et al, 2010), and bacteria such as Escherichia coli (Wooley et al, 2000;Montgomery et al, 2005;Oh et al, 2012), Francisella spp. (Nix et al, 2006), Yersinia enterocolítica (Townsend et al, 2008), Campylobacter jejuni (Stewart-Tull et al, 2009), Staphylococcus aureus (Polakowska et al, 2012), Riemerella anatipestifer (Seo et al, 2013) and Listeria monocytogenes (Andersson et al, 2015). In the case of Enterococcus spp., Borst et al (2014) reported that the ELA is able to differentiate between virulent and avirulent strains, whose genotype has been closely related to each other through pulsedfield gel electrophoresis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation